2023
DOI: 10.3390/jcm12072672
|View full text |Cite
|
Sign up to set email alerts
|

Access to High-Cost Biological Agents: Perceptions of Brazilian Patients with Inflammatory Bowel Diseases

Abstract: Background and aims: Brazilian patients with inflammatory bowel diseases (IBD) requiring therapy with biological agents usually have access to medicines through the National Unified Health Care System (SUS). This study aimed to analyze Brazilian IBD patient perception regarding access (availability and provision quality) to high-cost drugs in the public health care system. Methods: A questionnaire-based survey was carried out in an IBD referral center in Brazil. All adult patients with an established diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…This is in accordance with the few available epidemiological data from Brazilian cohorts. [52][53][54][55] In contrast, data from European cohorts reflect a different scenario possibly caused by the current epidemiological stage of the disease in this region and/or income status in the region. 56 An IBD Swiss cohort study reported that 26%-50% of CD patients had inflammatory behavior with perianal disease ranging from 3.7% to 26% 57,58 and that 37.5% of the UC patients had pancolitis.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the few available epidemiological data from Brazilian cohorts. [52][53][54][55] In contrast, data from European cohorts reflect a different scenario possibly caused by the current epidemiological stage of the disease in this region and/or income status in the region. 56 An IBD Swiss cohort study reported that 26%-50% of CD patients had inflammatory behavior with perianal disease ranging from 3.7% to 26% 57,58 and that 37.5% of the UC patients had pancolitis.…”
Section: Discussionmentioning
confidence: 99%